2007
DOI: 10.1590/s0100-736x2007001200004
|View full text |Cite
|
Sign up to set email alerts
|

Mecanoreceptores da mucosa palatina de avestruz (Struthio camelus): estudo ao microscópio de luz

Abstract: Foram estudados corpúsculos de Herbst da mucosa palatina de avestruz em nível de microscopia de luz. Os corpúsculos compõem-se de uma cápsula externa, cápsula interna e axônio central. A cápsula externa apresentou numerosas lamelas, enquanto que a cápsula interna mostrou estrutura de folhas compactas. Os corpúsculos apresentaram formato ovalado ou circular e circundado por espessos feixes de fibras colágenas. Cada lamela estava composta de uma densa rede de fibras espessas. Os axônios terminais estavam situado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…This differs from the Herbst corpuscles depicted in the bill tip organ in the kiwi (Cunningham et al, ) and in other birds (Bolze, ; Cobb and Bennett, ; Watanabe et al, ; Toyoshima et al, ; Halata and Grim, ) where the outer zone is relatively narrow and the inner core forms a considerable component of the corpuscle. This feature of a larger outer zone and smaller inner core was briefly noted by Guimarães et al () when comparing the Herbst corpuscles in the ostrich palate to those in the chicken. As in the capsule of the ostrich, a fibroblast displaying a sensory cilium was identified in the outer zone, a phenomenon not previously reported in avian Herbst corpuscles.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This differs from the Herbst corpuscles depicted in the bill tip organ in the kiwi (Cunningham et al, ) and in other birds (Bolze, ; Cobb and Bennett, ; Watanabe et al, ; Toyoshima et al, ; Halata and Grim, ) where the outer zone is relatively narrow and the inner core forms a considerable component of the corpuscle. This feature of a larger outer zone and smaller inner core was briefly noted by Guimarães et al () when comparing the Herbst corpuscles in the ostrich palate to those in the chicken. As in the capsule of the ostrich, a fibroblast displaying a sensory cilium was identified in the outer zone, a phenomenon not previously reported in avian Herbst corpuscles.…”
Section: Discussionsupporting
confidence: 63%
“…Based on these studies, the Herbst corpuscles of neognaths demonstrate the following general structural features: a central axon surrounded by an inner core formed by specialized Schwann cells, an outer zone which contains collagen fibers and surrounds the lamellated inner core, and an outer capsule derived from the perineurium (Gottschaldt, ; Malinovský and Páč, ). The basic structure of Herbst corpuscles in the oropharynx of ratites has been briefly described by light microscopy in the ostrich ( Struthio camelus ) (Palmieri et al, ; Tivane et al, ; Guimarães et al, ; Tivane, ), emu ( Dromaius novaehollandiae ) (Crole, ; Crole and Soley, ), and greater rhea ( Rhea americana ) (Feder, ) as well as in the bill of the kiwi ( Apteryx spp.) (Cunningham et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The collared peccary lips (Teófilo et al., ) as well as the palate showed that its oral mucosa is rich in mechanoreceptors. Although Meissner, Paccini and Ruffini types are often associated with the oral mucosa (Halata et al., ; Jayawardena et al., ; Watanabe, ; Guimarães et al., ; Teófilo et al., ), in the present study pacinian corpuscles were the most frequently observed. It is known that the mechanoreceptors are important for the sensorimotor regulation of oral behaviour (Trulsson and Johansson, ).…”
Section: Discussioncontrasting
confidence: 39%
“…Palmieri et al () and Tivane et al () noted a particular concentration of Herbst corpuscles in the median palatine ridge of the nonglandular region in the oropharyngeal roof of the ostrich. Guimarães et al () reported on the presence of Herbst corpuscles in the caudal third of the ostrich oropharyngeal roof. However, as revealed by other studies in this species (Tivane et al, ; Tivane, ; Crole and Soley, ), the distribution of these structures is far more widespread.…”
Section: Introductionmentioning
confidence: 99%